1997
DOI: 10.1021/ma970802n
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of PSS/PDADMAC-co-AA Polyelectrolyte Complexes and Their Stoichiometry Using Analytical Ultracentrifugation

Abstract: Analytical ultracentrifugation was successfully applied to the determination of the complex composition and characterization of the particles of water insoluble polyelectrolyte complexes between sodium poly(styrenesulfonate) (PSS) and copolymers of various ratios of diallyldimetylammonium chloride (DADMAC) and acrylamide (AA). Sedimentation velocity experiments in an analytical ultracentrifuge with absorption optics allow the observation of individual species in a system of strongly polydisperse, aggregated pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 12 publications
(29 reference statements)
3
71
1
Order By: Relevance
“…It is worth mentioning that the formation of similar aggregated structures was also observed for other pairs of oppositely charged polyelectrolytes, in particular, for Fig. 2 The dependence of the optical density OD 500 obtained for mixtures of P(DMDAAáCl) and P(MaáNa-co-Pr) on the concentration of NaCl OD 343 is the optical density measured at 343 nm and x is the distance from the meniscus of the sedimentation cell poly(sodium styrenesulfonate) and P(DMDAAáCl) [19,20].…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…It is worth mentioning that the formation of similar aggregated structures was also observed for other pairs of oppositely charged polyelectrolytes, in particular, for Fig. 2 The dependence of the optical density OD 500 obtained for mixtures of P(DMDAAáCl) and P(MaáNa-co-Pr) on the concentration of NaCl OD 343 is the optical density measured at 343 nm and x is the distance from the meniscus of the sedimentation cell poly(sodium styrenesulfonate) and P(DMDAAáCl) [19,20].…”
Section: Resultssupporting
confidence: 53%
“…4, 5). It is worth mentioning that similar inferences (but only for the case when the ionic strength of the surrounding medium is not extremely low) were drawn with respect to aggregated structures that appear as a result of electrostatic interaction between poly(styrene sulfonate) and P(DMDAAáCl) [19,20]. Table 1 contains the values of OD 500 obtained for the mixtures of P(DMDAAáCl) and P(MaáNa-co-Pr) prepared according to two dierent procedures, i.e., method A and method B, as well as the values of R H measured for the IPEC particles formed in these mixtures.…”
Section: Resultsmentioning
confidence: 65%
“…[8,11] Electrophoretic light scattering, [24,25] viscometry [12] and analytical ultracentrifugation [26] showed excess binding of the major component and a corresponding overcharging of the PEC particles. Obviously, the PEC particles consist of a charge neutralized core surrounded by a shell of attached chains of the excess component, which stabilize the particles against further aggregation.…”
Section: General Backgroundmentioning
confidence: 99%
“…The strong ionic bindings and the high cooperativity result in frozen structures. Previous studies [9][10][11][12][13][14] showed that the PEC particles consist of a neutralized, stoichiometric core and a shell of the excess component, which stabilizes the particles against further coagulation. At the 1 : 1 mixing ratio of anionic to cationic groups macroscopic flocculation occurs.…”
Section: Introductionmentioning
confidence: 99%